MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MELALUI PROBLEM BASED LEARNING (PBL) DENGAN BANTUAN LKPD DI SMKN 3 KOTA BLITAR SECARA DARING - Agustin Nafelia (JUSEDA, 2020)
The aim of this research to improving problem solving skills of student grade X smkn 3 blitar with applied problem based learning model assisted LKPD. This research is classroom action research which in three cycle. Each cycle consist of three steps, according to Kemmis and taggart are planning acting ang observing and reflecting. Subject of this research is class X KKR smkN 3 blitar odd semester which amount 35 students. Data obtained from observation form problem solving skill of students. The result of this research problem based learning model can improve problem solving skills of atudent class X.... this is evidenced with improving problem solving skill of students at first cycle, percentage all of indicators achieve 39%.. at second cycle improved 23% to be 62% and third cycle improved 33% to be 95%. This Research is stopped at third cycle because it was successful to reach indicator of problem solving skill of students that is minimum 75%.